PROTRACTED TRANSMISSION AND PERSISTENCE OF ST80 VANCOMYCIN-RESISTANT Enterococcus faecium CLONAL COMPLEX TYPES CT2933, CT2932 AND CT1916 IN A LARGE IRISH HOSPITAL: A 39-MONTH WGS STUDY - Coleman, David; Kinnevey, Peter (My University, 2024)
Background: Vancomycin-resistant Enterococcus faecium (VREfm) are significant nosocomial pathogens. Sequence type (ST)80 vanA-encoding VREfm predominate in Irish hospitals, but their transmission is poorly understood. Aims: To investigate transmission and persistence of predominant complex type (CT) VREfm in two wards of an Irish hospital (H1) using whole-genome sequencing, and their intra- and inter-hospital dissemination. Methods: Rectal screening (N=330, September 2019-December 2022) and environmental (N=48, November 2022-December 2022) E. faecium were investigated. Isolate relatedness was assessed by core-genome multilocus sequence typing (cgMLST) and core-genome single nucleotide polymorphism (cgSNP) analysis. Likely transmission chains were identified using SeqTrack (https://graphsnp.fordelab.com/graphsnp) using cgSNP data and recovery location. Well-characterised E. faecium (N=908) from seven Irish hospitals including H1 (June 2017-July 2022) were also investigated. Findings: Conventional MLST assigned isolates to nine STs (ST80, 82%). cgMLST identified three predominant ST80 CTs (CT2933, CT2932 and CT1916) (55% of isolates) of related isolates (≤20 allelic differences). cgSNP analysis differentiated these CTs into multiple distinct closely related genomic clusters (≤10 cgSNPs). Parisimonious network construction identified 55 likely inter- and intra-ward transmissions with epidemiological support between patients ≤30 days involving 73 isolates (≤10 cgSNPs) from seven genomic clusters. Numerous other likely transmissions over longer time periods without evident epidemiological links were identified, suggesting persistence and unidentified reservoirs contribute to dissemination. The three CTs predominated among E. faecium (N=1,286) in seven hospitals, highlighting inter-hospital spread without known epidemiological links. Conclusion: This study revealed the long-term intra- and inter-hospital dominance of three major CT ST80 VREfm lineages, widespread transmission and persistence, implicating unidentified reservoirs.
PUBLISHED
27th June 2024; Pub ahead of print
Keywords: VREfm, Vancomycin-resistant Enterococcus faecium, cgMLST, cgSNP analysis, environmental persistence, hospital transmission, whole-genome sequencing; Genes & Society; Immunology, Inflammation & Infection; Health